Implementasi Robot Manipulator menggunakan Sinyal Electromyography berdasarkan Pergerakan Kaki Manusia - Andre Adikusuma; Edita Rosana Widasari; Eko Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Technological developments in the medical field have developed rapidly, one example is the manipulator robot. For example, in some cases there are people suffering from stroke who have difficulty moving their limbs. Due to the limited number of rehabilitators, the rehabilitation process took longer and they had to wait in line to carry out rehabilitation. The movement of the robotic manipulator's leg will be based on the movement of the human leg by reading electromyography (EMG) signals generated from the leg muscles through the electrodes. Then an exponential filter is used to reduce the noise from the EMG signal. After filtering the signal obtained will be classified using a decision tree classification. Then the AX-12A servo is used to move the legs of the manipulator robot which has 4 degrees of freedom. The results of the decision tree classification have amplitude values for each movement, which include 0V to 1.995V as a squatting movement with an angle of 450; 1.995V to 2.985V as a 90Â° seated motion; 2.985V to 5V as a standing movement with an angle of 1800. The test results obtained determine the movement of the leg robot has an accuracy of 70.667% for the total average accuracy. The subjects used were 10 with 5 movements at each angle.